Development and validation of a ζ-globin-specific ELISA for carrier screening of the (−−SEA) α thalassaemia deletion. Issue 2 (29th January 2009) - Tang, L; Zhu, P; Zhou, W J; Zheng, J; Zhou, Y Q; Fu, N; Xu, X M
Abstract : Aims: The Southeast Asian (SEA) deletion (−− SEA ) represents the most common determinant causing α thalassaemia in Southeast Asian countries. The embryonic ζ-globin chain has been defined as a marker for the detection of this deletion in adults. The aim of this study was to develop an appropriate low-cost ELISA for ζ-globin chain detection as a routine screening test for (−− SEA ) α thalassaemia deletion. Methods: A sandwich ELISA system for ζ-globin chains was established with a pair of ζ-globin-specific monoclonal antibodies prepared in-house, and locally made products. Against a gap-PCR method that was taken as the standard, this assay was validated in a cohort study testing a total of 526 individuals comprising patients scheduled for haemoglobinopathy diagnostic analysis and normal individuals. Routine screening of the (−− SEA ) deletion in 300 random student volunteers was conducted using the assay. Results: While the cut-off point was set at a percentage positive value of 30, the sensitivity and specificity of this ELISA method were 100% and 99.24%, respectively. The mean intra-assay and inter-assay coefficients of variation among the different concentrations in the optimised ELISA conditions were 2.1–11.4% and 4.3–13.2%, respectively. Seventeen of the 300 volunteers sampled were determined by the ELISA to have the (−− SEA ) deletion; these results were in 100% agreement with the gap-PCR results. Conclusions: This study validates the ELISA method described here as a simple, rapid and cost-effective assay that is potentially adaptable for application in large-scale population screening for this prevalent disorder in SEA areas such as southern China.